Association between diet and quality of life among healthcare professionals in King Saud University Medical City - Waad Alfawaz; Reem S. Albassam; Noura Almuharib; Shuruq Alghafis; Walaa Mahfouz (Frontiers in Public Health)
BackgroundA balanced diet and active lifestyle are key factors influencing health and quality of life (QoL). This study examined the relationships between eating patterns, physical activity, and QoL among Arab healthcare professionals.MethodologyA cross-sectional study included 353 healthcare workers in Riyadh, Saudi Arabia. Data were collected through face-to-face interviews, where participants were briefed on the study objectives and provided voluntary informed consent. The WHOQOL-BREF tool was used to evaluate QoL, while the Rapid Diet Quality Screener assessed dietary habits. The Global Physical Activity Questionnaire was used to measure physical activity. Statistical analysis included independent samples t-tests, one-way ANOVA, and Pearson correlation.ResultsAmong participants, 47.6% had a normal weight, 44.7% were overweight or obese, and 7.6% were underweight. While those with normal weight had the highest QoL scores across all domains, differences across BMI categories were not statistically significant. Regular physical activity was linked to high QoL, particularly in social relationships (p = 0.037). Participants who exercised regularly also reported healthier eating habits (p < 0.001). Weak but significant positive correlations were found between diet quality and QoL, particularly physical health (r = 0.219, p < 0.001) and psychological health (r = 0.184, p = 0.002). No significant diet quality differences were found between genders (p = 0.677).ConclusionHealthcare professionals who exercise regularly exhibit a better QoL, especially in social relationships, and maintain healthier eating habits. While normal BMI was associated with improved QoL, differences across BMI categories were not statistically significant. These findings highlight the need for interventions promoting physical activity and healthy eating to enhance QoL in healthcare workers.